Positive electrode active material composition for lithium secondary battery and lithium secondary battery including the same

By adjusting Ni compositions and heat treatment temperatures for large and small particles in the positive electrode active material, the battery achieves improved output and lifespan, addressing the challenges of cost and stability in lithium secondary batteries.

JP2024174179APending Publication Date: 2024-12-13ECOPRO BM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024173137
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-05-23
Filing Date
2024-10-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lithium secondary batteries face challenges with high costs and unstable supply of cobalt due to its limited reserves, and the use of alternative materials like LiMnO2 and LiNiO2 faces issues with cycle characteristics and manufacturing costs, while optimizing particle sizes and heat treatment temperatures is difficult to achieve optimal performance in mixed compositions.

Method used

A positive electrode active material composition is developed with adjusted nickel (Ni) compositions and proportions for large and small particles, optimized through specific heat treatment temperatures, ensuring similar optimal capacity development temperatures for both sizes, enhancing output and lifespan.

Benefits of technology

The adjusted Ni composition and heat treatment process result in a lithium secondary battery with improved output and lifespan by optimizing the performance of mixed particle sizes, achieving enhanced capacity and life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174179000001_ABST
    Figure 2024174179000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material composition for a lithium secondary battery and a lithium secondary battery including the same, and more specifically, a positive electrode active material composition for a lithium secondary battery and a lithium secondary battery including the same including a mixture of particles heat treated at the same temperature with different Ni composition and particle size.SOLUTION: According to the present invention, it is possible to adjust the Ni content of large particles and small particles to similarly adjust the optimum volume development temperature of large particles and small particles, thereby manufacturing a lithium secondary battery having improved output and life.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material composition for a lithium secondary battery and a lithium secondary battery including the same, and more particularly to a positive electrode active material composition for a lithium secondary battery comprising a mixture of particles having different Ni compositions and sizes but prepared at the same heat treatment temperature, and a lithium secondary battery including the same. [Background technology]

[0002] Secondary batteries, especially lithium secondary batteries, are widely used in the field of small, advanced electronic devices such as mobile devices and notebook computers. Medium and large-sized batteries are also being developed, but with the spread of electric vehicles (EVs), the development of high-capacity, electrochemically stable lithium secondary batteries is particularly in progress.

[0003] Among the components of a lithium secondary battery, the positive electrode active material plays an important role in determining the capacity and performance of the battery.

[0004] Secondary battery manufacturers are increasing the capacity of secondary batteries by improving the mixture density of the positive electrode plate based on optimizing the average particle size and particle size distribution of the positive electrode active material.

[0005] In the positive electrode active material, lithium cobalt oxide (LiCoO2), which has relatively excellent physical properties such as excellent cycle characteristics, is mainly used, but cobalt used in LiCoO2 is a so-called rare metal, and has a small reserve and uneven production area, which causes a problem of unstable supply. In addition, due to the unstable supply of cobalt and the increasing demand for lithium secondary batteries, LiCoO2 is expensive.

[0006] In this context, research into positive electrode active materials that can replace LiCoO2 has been steadily progressing, and the use of lithium-containing manganese oxides such as LiMnO2 and LiMn2O4 with a spinel crystal structure, as well as lithium-containing nickel oxide (LiNiO2) has also been considered. However, due to the characteristics of its manufacturing method, it is difficult to apply LiNiO2 to actual mass production processes at a reasonable cost, and lithium manganese oxides such as LiMnO2 and LiMn2O4 have the disadvantage of poor cycle characteristics.

[0007] As a result, recent research has focused on using lithium transition metal composite oxides or lithium transition metal phosphates containing two or more of the transition metals nickel (Ni), manganese (Mn), and cobalt (Co) as the positive electrode active material as representative alternative materials. In particular, research into the use of layered oxides of the three components Ni, Mn, and Co has progressed steadily.

[0008] Meanwhile, in order to increase the energy density of the positive electrode active material, it is advantageous to increase the density by appropriately mixing large particles and small particles. Large particles and small particles have their own optimal heat treatment temperatures depending on the nickel (Ni) content, and since small particles have a larger specific surface area than large particles, they can absorb a lot of lithium (Li) even at a relatively low heat treatment temperature. However, the temperature range at which the small particles exhibit their optimal capacity is lower than that of the large particles.

[0009] In addition, since the temperature range at which the mixed composition exhibits optimal performance depends on the temperature of the large particles, which are mixed at a high ratio, it is difficult for small particles, which are mixed at a relatively low ratio, to exhibit optimal performance in the mixed composition.

[0010] Therefore, there is a need to develop a positive electrode active material that can simultaneously satisfy the optimum temperatures for both large and small particles.

[0011] As a result of intensive research and efforts made by the present inventors to overcome the problems of the above-mentioned conventional techniques, it was found that in the case of a positive electrode active material composition for a lithium secondary battery in which the Ni composition of large and small particles and the ratio of small particles in the mixed composition are adjusted, a mixed composition having improved output and life can be prepared by adjusting the Ni composition of large and small particles and optimizing the heat treatment temperature, and thus the present invention has been completed. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Republic of Korea Patent Publication No. 10-2014-0098433 Summary of the Invention [Problem to be solved by the invention]

[0013] In order to solve the above-mentioned problems of the conventional art, the present invention aims to provide a new positive electrode active material composition in which particles of different sizes are mixed, and the composition is varied depending on the particle size.

[0014] Another object of the present invention is to provide a lithium secondary battery containing the positive electrode active material. [Means for solving the problem]

[0015] In order to solve the above problems, the present invention provides Particle 1 represented by the following chemical formula 1 and In a positive electrode active material composition comprising particles 2 represented by the following chemical formula 2,

[0016] [ka]

[0017] [ka]

[0018] (In the above chemical formulas 1 and 2, 0.6≦x1≦0.99, 0.59≦x2≦0.98, 0.5≦a1≦1.5, 0.5≦a2≦1.5, 0.0≦y1≦0.3, 0.0≦y2≦0.3, 0.0≦z1≦0.3, 0.0≦z2≦0.3, 0.0≦1-x1-y1-z1≦0.3, 0.0≦1-x2-y2-z2≦0.3, M is one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof. The positive electrode active material is provided such that x1 and x2 satisfy the condition 0.01≦x1−x2≦0.4.

[0019] Conventionally, in a mixed composition of large and small particles, the temperature ranges at which the large and small particles exhibit their optimal capacity are different and depend on the temperature range of the large particles having a higher mixing ratio, making it difficult to achieve optimal performance of the small particles in the mixed composition.

[0020] Therefore, the inventors have confirmed that it is possible to manufacture a lithium secondary battery having improved output and life by adjusting the nickel (Ni) composition of the large particles and the small particles to adjust the optimal capacity of the large particles and the small particles, and by making the heat treatment temperature of the large particles and the small particles the same, thereby completing the present invention.

[0021] In the positive electrode active material composition for a lithium secondary battery according to the present invention, the above-mentioned x1 and x2 satisfy the condition 0.01≦x1−x2≦0.4.

[0022] That is, in the positive electrode active material composition for a lithium secondary battery of the present invention, the Ni composition of the particles 2 is 1 to 40% lower than the Ni composition of the particles 1, and is preferably 5 to 40% lower.

[0023] The positive electrode active material composition for a lithium secondary battery of the present invention is characterized in that the ratio of the particles 2 is 1 to 40% by weight, preferably 5 to 40% by weight, based on the total weight of the mixed composition.

[0024] According to one experimental example of the present invention, the optimum capacity depending on the proportion of small particles in a mixed composition was confirmed. The results showed that the optimum capacity was expressed when the Ni composition of the small particles was 5% lower than that of the large particles and the proportion of the small particles was 20 to 40%, whereas the optimum capacity could not be expressed when the Ni composition of the small particles was the same as that of the large particles or was 10 mol% lower, even if the proportion of the small particles was 20 mol%.

[0025] In addition, it was confirmed that the output and life characteristics were improved when the Ni composition of the small particles was 5% lower than that of the large particles and the ratio of the small particles was 20%. This result means that the mixed composition can only achieve optimal capacity and improve output and life characteristics when the Ni composition of the small particles relative to the large particles and the ratio of the small particles mixed in the total particles are all satisfied.

[0026] In the positive electrode active material composition for a lithium secondary battery of the present invention, the size of the particle 1 represented by the chemical formula 1 is 6 μm to 30 μm, and the size of the particle 2 represented by the chemical formula 2 is 1 μm to 6 μm.

[0027] The size of Particle 1 represented by Chemical Formula 1 and the size of Particle 2 represented by Chemical Formula 2 according to the present invention represent D50 values ​​analyzed by a particle size analyzer.

[0028] The positive electrode active material composition for a lithium secondary battery of the present invention is characterized in that the overall average Ni molar fraction of the positive electrode active material composition for a lithium secondary battery is 60 to 99%.

[0029] The positive electrode active material composition for a lithium secondary battery of the present invention is characterized in that the large particles and small particles of the positive electrode active material according to the present invention have an optimum capacity development temperature of 860 to 720°C.

[0030] According to an experimental example of the present invention, the optimum capacity manifestation temperature according to the nickel content of the first heat-treated product was confirmed, and it was confirmed that the temperature at which the optimum performance of the first heat-treated product is manifested varies depending on the nickel content. In addition, it was confirmed that the optimum capacity manifestation temperatures of the large particles and the small particles are similar when the nickel content of the small particles is 5% lower than that of the large particles. This result means that by adjusting the nickel content of the small particles so that the optimum capacity manifestation temperature is similar to that of the large particles, the first heat treatment temperature can be made similar, and as a result, the optimum performance of the small particles can be maximized.

[0031] The present invention further provides a lithium secondary battery comprising the positive electrode active material composition.

[0032] The present invention further comprises: preparing a precursor composition by mixing a first precursor represented by the following formula 3 and a second precursor represented by the following formula 4;

[0033] [ka]

[0034] [ka]

[0035] (In the above chemical formulas 3 and 4, 0.6≦x1≦0.99, 0.59≦x2≦0.98, 0.0≦y1≦0.3, 0.0≦z1≦0.3, 0.0≦1-x1-y1-z1≦0.3, 0.0≦y2≦0.3, 0.0≦z2≦0.3, and 0.0≦1-x2-y2-z2≦0.3, M is one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof. mixing a lithium compound with the precursor composition and subjecting the mixture to a first heat treatment at a first temperature; and mixing the mixture with one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and subjecting the mixture to a second heat treatment at a second temperature.

[0036] The method for preparing a positive active material composition according to the present invention may further include washing the mixture after the second heat treatment with distilled water and drying it.

[0037] The method for preparing a cathode active material composition according to the present invention includes preparing a first precursor and a second precursor having different particle sizes and Ni contents, mixing the first precursor and the second precursor, and then subjecting the first precursor and the second precursor to a first heat treatment at the same temperature.

[0038] The positive electrode active material composition for a lithium secondary battery of the present invention is characterized in that the large particles and small particles of the positive electrode active material according to the present invention have an optimum capacity development temperature of 860 to 720°C.

[0039] In the present invention, the optimum capacity manifestation temperature according to the nickel content of the positive electrode active material was confirmed. As a result, it was confirmed that the temperature at which the heat-treated product manifests optimum performance varies depending on the nickel content, and when the nickel content of the small-sized particles is 5% lower than the nickel content of the large-sized particles, the optimum capacity manifestation temperatures of the large-sized particles and the small-sized particles are similar.

[0040] Thus, the present invention is characterized in that the nickel content of the small-sized particles is adjusted to make the optimum capacity manifestation temperature similar to that of the large-sized particles, and the first precursor and the second precursor are first heat-treated at the same temperature, so that the small-sized particles also exhibit their optimum capacity, thereby allowing the positive electrode active material composition to exhibit its optimum performance.

[0041] In the method for producing a positive electrode active material composition according to the present invention, the x1 and x2 satisfy the condition 0.01≦x1−x2≦0.4.

[0042] In the method for producing a positive electrode active material composition according to the present invention, in the step of mixing the precursor composition, the second precursor is mixed in a ratio of 5 to 40% by weight with respect to the total weight of the precursor composition.

[0043] In the method for producing a positive electrode active material composition according to the present invention, the size of the first precursor particles represented by the chemical formula 3 is 6 μm to 30 μm, and the size of the second precursor particles represented by the chemical formula 4 is 1 μm to 6 μm. Effect of the Invention

[0044] The positive electrode active material composition for a lithium secondary battery according to the present invention is composed of a mixture of particles having different sizes, and by adjusting the Ni composition of the small sized particles relative to the Ni composition of the large sized particles and the mixing ratio of the small sized particles to the total mixture composition, the optimum capacity manifestation temperature can be similarly adjusted, thereby making it possible to manufacture a lithium secondary battery having improved output and life span. [Brief description of the drawings]

[0045] [Figure 1] FIG. 1 is a graph showing the results of confirming the discharge capacity of the positive electrode active material of the present invention as a function of heat treatment temperature. [Diagram 2] 1 is a photograph of the positive electrode active material of the present invention (Example 1) taken by SEM. [Diagram 3] FIG. 2 is a diagram showing the results of confirming optimal capacity expression of a lithium secondary battery including the mixed composition of the present invention. [Figure 4] FIG. 2 is a diagram showing the results of confirming the output characteristics of a lithium secondary battery including the mixed composition of the present invention. [Diagram 5] FIG. 2 is a diagram showing the results of confirming the life characteristics of a lithium secondary battery containing the mixed composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] The present invention will be described in more detail below with reference to examples. These examples are merely intended to illustrate the present invention, and therefore the scope of the present invention is not to be construed as being limited by these examples.

[0047] Manufacturing example: Manufacturing of positive electrode active material To prepare the positive electrode active material, a precursor represented by NiCoMn(OH)2 was prepared by coprecipitation. The Ni composition of the precursor was as shown in Table 1 below.

[0048] [Table 1]

[0049] The lithium compound LiOH or Li2CO3 was added to the prepared precursor, and the precursor was subjected to a first heat treatment at a heating rate of 1℃ / min~20℃ / min for 4~20 hours (maintenance period) in the presence of N2, O2 / (1~100LPM), and then a compound containing Al was mixed at 0~10mol% and subjected to a second heat treatment to prepare a positive electrode active material for lithium secondary batteries.

[0050] Next, distilled water was prepared and kept at a constant temperature of 5 to 40° C., and then the prepared positive electrode active material for a lithium secondary battery was put into the distilled water and washed for 0.1 to 10 hours while maintaining the temperature.

[0051] The washed positive electrode active material was passed through a filter press and then dried at 50 to 300° C. for 3 to 24 hours.

[0052] Experimental Example 1: Confirmation of optimum capacity manifestation temperature and discharge capacity An experiment was carried out to confirm the primary heat treatment temperature at which the optimal capacity of the particles of Preparation Examples 1 to 12 is realized.

[0053] In addition, a battery containing the prepared particles was manufactured and the capacity was measured. The results are shown in Table 2 and FIG.

[0054] [Table 2]

[0055] As a result, as can be seen from Table 2 and FIG. 1, when the Ni content of the small particles is about 5% lower than that of the large particles, the first heat treatment temperature at which the small particles exhibit their optimum capacity is similar to that of the large particles.

[0056] Comparative Examples 1 to 4 and Examples 1 to 6: Preparation of Mixed Positive Electrode Active Material Compositions A precursor was first prepared according to the Ni composition in Table 3 below. Next, a lithium compound such as LiOH or Li2CO3 was added to the precursor prepared above, and the precursor was subjected to a first heat treatment at a heating rate of 1°C / min to 20°C / min for 4 to 20 hours (maintenance period) in the presence of N2, O2 / (1 to 100 LPM), and then a compound containing Al was mixed in an amount of 0 to 10 mol% and subjected to a second heat treatment to prepare a positive electrode active material for a lithium secondary battery.

[0057] Next, distilled water was prepared and kept at a constant temperature of 5 to 40° C., and then the prepared positive electrode active material for a lithium secondary battery was put into the distilled water and washed for 0.1 to 10 hours while maintaining the temperature.

[0058] The washed positive electrode active material was passed through a filter press and then dried at 50 to 300° C. for 3 to 24 hours.

[0059] [Table 3]

[0060] Experimental Example 2: SEM Measurement of Positive Electrode Active Material In order to confirm the particle size of all the positive electrode active materials (Example 1) prepared in the above Example, the particles were observed with a scanning electron microscope (SEM), and the results are shown in FIG.

[0061] Manufacturing example: Battery manufacturing Batteries were constructed containing the following mixed positive electrode active material composition: 1) Positive electrode slurry production [5g standard] and electrode plate production 94wt.% active material, 3wt.% conductive agent (super-P), and 3wt.% binder (PVDF) are mixed at 4.7g:0.15g:0.15g ratio using an auto mixer at 1900rpm / 10min. Next, apply to Al-foil [15μm] and press with a micro film applicator to create a film. After creation, dry in a dry oven at 135℃ for 4 hours. 2) Coin cell production The positive electrode is a coated plate with an area of ​​2 cm 2 The negative electrode is made of lithium metal foil, the separator is made of W-Scope-20μm polypropylene, and the electrolyte is made of 1.15M LiPF6 with a composition of in EC / EMC=7 / 3. Coin-cell size is made of CR2016 and CR2032 type, and assembled in an argon-filled glove box in the usual way.

[0062] Experimental Example 3: Confirmation of optimal capacity depending on the ratio of small particles in the mixed composition The optimum capacity of the coin cells of Examples 1 to 6 and Comparative Examples 1 and 4 was confirmed, and the results are shown in Table 4 and FIG.

[0063] [Table 4]

[0064] As can be seen from Table 4 and FIG. 3, it was confirmed that the Ni composition of the small particles is 5% lower than that of the large particles, and the optimum capacity is expressed when the proportion of the small particles in the mixed composition is 20%.

[0065] Experimental Example 4: Confirmation of output characteristics of large and small particle mixture composition The output characteristics of the coin cells of Examples 1 to 6 and Comparative Examples 1 and 4 were confirmed, and the results are shown in Table 5 and FIG.

[0066] [Table 5]

[0067] Experimental Example 5: Lifetime characteristics of large and small particle mixture composition The life characteristics of the coin cells of Examples 1 to 6 and Comparative Examples 1 and 4 were confirmed, and the results are shown in Table 6 and FIG.

[0068] [Table 6]

[0069] As a result, as can be seen from Table 6 and FIG. 5, Example 2 has the longest life.

Claims

1. Particle 1 represented by the following chemical formula 1, In a positive electrode active material composition composed of particles 2 represented by the following chemical formula 2, 【Chemistry 1】 【Chemistry 2】 (In the above chemical formulas 1 and 2, 0.6≦x1≦0.99, 0.59≦x2≦0.98, 0.5≦a1≦1.5, 0.5≦a2≦1.5, 0.0≦y1≦0.3, 0.0≦y2≦0.3, 0.0≦z1≦0.3, 0.0≦z2≦0.3, 0.0≦1-x1-y1-z1≦0.3, and 0.0≦1-x2-y2-z2≦0.3, M is one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof. The positive electrode active material composition, wherein x1 and x2 satisfy the condition 0.01≦x1−x2≦0.

4.

2. 2. The positive electrode active material composition for a lithium secondary battery according to claim 1, wherein the particles 2 are mixed in an amount of 5 to 40% by weight based on the total weight of the positive electrode active material composition.

3. 2. The positive electrode active material composition for a lithium secondary battery according to claim 1, wherein the size of Particle 1 represented by Chemical Formula 1 is 6 μm to 30 μm, and the size of Particle 2 represented by Chemical Formula 2 is 1 μm to 6 μm.

4. A lithium secondary battery comprising the positive electrode active material composition according to any one of claims 1 to 3.

5. preparing a precursor composition by mixing a first precursor represented by the following Chemical Formula 3 and a second precursor represented by the following Chemical Formula 4; 【Chemistry 3】 【Chemistry 4】 (In the above chemical formulas 3 and 4, 0.6≦x1≦0.99, 0.59≦x2≦0.98, 0.0≦y1≦0.3, 0.0≦y2≦0.3, 0.0≦z1≦0.30.0.0≦z2≦0.3, 0.0≦1-x1-y1-z1≦0.3, and 0.0≦1-x2-y2-z2≦0.3, M is one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof. mixing a lithium compound with the precursor composition and subjecting the mixture to a first heat treatment at a first temperature; mixing one or more elements selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, with the lithium compound and the precursor composition mixture, and performing a second heat treatment at a second temperature; washing the second heat-treated mixture with distilled water and drying; A method for producing a positive electrode active material composition comprising the steps of:

6. 6. The method for producing a positive electrode active material composition according to claim 5, wherein the x1 and x2 satisfy the condition 0.01≦x1−x2≦0.

4.

7. 6. The method for producing a positive electrode active material composition according to claim 5, wherein in the step of mixing the precursor compositions, the second precursor is mixed in a ratio of 5 to 40 wt % with respect to a total weight of the precursor composition.

8. 6. The method for producing a positive electrode active material composition according to claim 5, wherein the size of the first precursor particles represented by Chemical Formula 3 is 6 μm to 30 μm, and the size of the second precursor particles represented by Chemical Formula 4 is 1 μm to 6 μm.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary battery and lithium secondary cell using the same

    JP2010086693A

  • Positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2019029205A

  • Positive electrode active material composition for lithium secondary battery and lithium secondary battery including the same

    JP6810120B2

  • Lithium-containing composite oxide and method for production thereof

    WO2008084679A1

  • Cathode active material for secondary battery with improved durability and lithium secondary battery including same

    KR1020140098433A